Strengthening and Developing Creative Economy Products Based on Regional Potential Resources In The Leading Subsectors of Baubau City - Supriyadi, Supriyadi; Saputra, Yusuf Jaya; Mujahid, Imam (Asian Journal of Social and Humanities, 2023)
One of the reasons for the development of the creative industry is its positive impact on social life, business atmosphere, economic improvement and regional image. Baubau Municipality as an autonomous region is one of the cities that has considerable creative city development potential and already has an economy development masterplan document. The problem that arises is that the knowledge of HR actors is still limited, and this is one aspect that causes business backwardness, in terms of protecting products/services in the creative economy sector of Baubau city, which is difficult to increase the scale of production of superior subsectors. In addition, there are still many works/products that do not state the work produced as the originality of the work/product. This research was motivated by the potential of the leading sector economy in Baubau City, Sultra. But unfortunately it still needs strengthening and development from several aspects. Therefore, the purpose of this study is to identify and analyze what are the priority problems in the development of works/products in Baubau City, and analyze the strengthening and development model of works/products based on potential sources of excellence in Baubau City. The targeted output in this study is articles in accredited national journals ranked 2 and an additional output in the form of a copyright certificate is planned.  The expected output from the results of the implementation of this research is in the form of strengthening models and developing potential resource-based export products in the leading subsector areas in Baubau City so that they can provide recommendations for local government study materials in making policies for the development of works / export products in their superior subsectors.